Legal Protection for Women in Criminal Proceedings: A Socio-Legal Review - Rahmi, Atikah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Women often become victims of crimes, especially sexual crimes and domestic violence, in legal proceedings, but the legal protection stipulated in laws and regulations is still considered inadequate and many women still experience discrimination and injustice. The purpose of this study is to analyze the legal protection of women victims in criminal justice proceedings in Indonesia from a socio-legal perspective in order to identify the socio-cultural-structural barriers that cause the weakness of such protection. This study uses an empirical legal research method with a sociological legal approach to analyze the application of regulations on protecting women victims in criminal proceedings, with primary data obtained from field studies and interviews which are then analyzed qualitatively. The results show that nomatively, regulations on protecting women victims are adequate, but in practice they are heavily influenced by patriarchal socio-cultural factors and negative stigma against women victims which affect the attitude of law enforcement officials, resulting in many victims experiencing discrimination and injustice. The socio-cultural-structural barriers include negative stigma and discriminatory treatment of victims, patriarchal culture that subordinates women, lack of psychosocial and legal support for victims, and limited access to justice for marginalized women victims. At the structural level there are also problems of low gender capacity of law enforcement officials, lack of NGO advocacy, and legal and judicial systems that are not yet victim-friendly.